2003
DOI: 10.1046/j.1365-277x.2003.00461.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient intakes of an adult Pakistani, European and African‐Caribbean community in inner city Britain

Abstract: The data provide nutrient intake estimates in three different ethnic groups using a similar method. Limitations include under-reporting across all ethnic groups in a similar pattern with under-reporters having higher BMIs in all groups, as found elsewhere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
62
7
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(80 citation statements)
references
References 29 publications
(61 reference statements)
8
62
7
1
Order By: Relevance
“…In a recent study of AfricanAmerican adults, Sharma et al described the main food sources for energy and fat intakes and demonstrated the importance of 'Western' foods such as sugar-sweetened beverages and burgers (11) , indicating significant dietary acculturation in African-Americans. The Child Heart and Health Study in England (CHASE) has described the nutritional composition of the diets of children of Black African and African-Caribbean ethnicity in England and corroborated earlier data (6) in recognising lower total and saturated fat intakes compared with White European children (12) . In further exploration of the nutritional data, Donin et al (13) reported that these differences in nutritional composition are more marked for Black African than Black Caribbean children, which could be a result of traditional cultural differences, or may be an effect of changes in dietary intake, or due to greater 'dietary acculturation' in the latter towards the diet of the general UK population given the earlier migration of this ethnic subgroup (13) .…”
mentioning
confidence: 55%
See 2 more Smart Citations
“…In a recent study of AfricanAmerican adults, Sharma et al described the main food sources for energy and fat intakes and demonstrated the importance of 'Western' foods such as sugar-sweetened beverages and burgers (11) , indicating significant dietary acculturation in African-Americans. The Child Heart and Health Study in England (CHASE) has described the nutritional composition of the diets of children of Black African and African-Caribbean ethnicity in England and corroborated earlier data (6) in recognising lower total and saturated fat intakes compared with White European children (12) . In further exploration of the nutritional data, Donin et al (13) reported that these differences in nutritional composition are more marked for Black African than Black Caribbean children, which could be a result of traditional cultural differences, or may be an effect of changes in dietary intake, or due to greater 'dietary acculturation' in the latter towards the diet of the general UK population given the earlier migration of this ethnic subgroup (13) .…”
mentioning
confidence: 55%
“…Previous studies have recognised distinct nutritional composition differences between native Caribbean and first-generation migrant Caribbean communities in the UK, suggesting that migration and the processes of acculturation (9) result in increasing intakes of energy, fat and saturated fat (8) ; although when compared with White Europeans, intakes of fat and saturated fat remain significantly lower in UK African-Caribbean adults (6) . Earlier studies describing important foods in the diets of firstgeneration migrants in the UK demonstrate the influence of traditional foods and dishes (6,10) but it is not clear whether these dietary patterns have changed in more recent years or in subsequent generations. In a recent study of AfricanAmerican adults, Sharma et al described the main food sources for energy and fat intakes and demonstrated the importance of 'Western' foods such as sugar-sweetened beverages and burgers (11) , indicating significant dietary acculturation in African-Americans.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…19 Our dietary data revealed a markedly lower intake of saturated fat and higher intake of CHO in South Asian and black African-Caribbean groups compared to whiteEuropean populations, an observation that is consistent with earlier findings. [31][32][33][34] Both the South Asian and black AfricanCaribbeans within the present study consumed diets that were relatively high in CHO and starch, with higher glycaemic loads. Further study is needed to determine the impact of these dietary features on Si and beta-cell function.…”
Section: Discussionmentioning
confidence: 91%
“…Additional questions were listed to ascertain the use of spreading and cooking fats, added sugar, other regularly consumed foods, special diets, changes in diet, use of food supplements and self-reported height and weight. A nutrient database was compiled using 'Microdiet' ('Microdiet 8.08' University of Salford, Salford, UK) with portion sizes derived from published data (28), from data compiled for the Manchester diabetes study (29) and from limited data in the questionnaire.…”
Section: Dietary Analysismentioning
confidence: 99%